High output stoma after surgery for rectal cancer - a risk factor for low anterior resection syndrome? - Xuena Zhang; Qingyu Meng; Jianna Du; Zhongtao Tian; Yinju Li; Bin Yu; Wenbo Niu (BMC Gastroenterology)
Abstract Purpose The relationship between high-output stoma (HOS) and low anterior resection syndrome (LARS) was previously unclear. This study investigated the association between HOS and major LARS in rectal cancer patients with preventive stoma. Methods We conducted a retrospective analysis of 653 rectal cancer patients who underwent prophylactic ileostomy reversal after low anterior resection at the Fourth Hospital of Hebei Medical University between 2018 and 2021. Patients were categorized into HOS and non-HOS groups based on stoma output within 3 months before surgery. Major LARS was assessed using the LARS score. The association between HOS and major LARS was analyzed using multifactor logistic regression models, subgroup analyses, and smoothing curve fitting methods. Results Among the 653 patients, 53 (8.1%) experienced HOS, and 81 (12.4%) developed major LARS after stoma closure. The HOS group exhibited a significantly higher risk of major LARS compared to the non-HOS group (P < 0.001). Multivariate logistic regression indicated that HOS was associated with a 210% increased risk of major LARS (OR: 3.10; 95% CI: 1.56, 6.14; P = 0.001). Subgroup analysis revealed that this association was more pronounced in older patients (age > 60), those without hypertension, with N0-N1 staging, a history of chemotherapy, and longer stoma closure intervals (Q3, Q4). Conclusion HOS is significantly associated with major LARS in rectal cancer patients, particularly in certain clinical subgroups. These findings suggest the need for careful management of HOS to potentially reduce LARS occurrence after stoma closure.